Law Enforcement Analysis against Notaries Who Do Negligence in Depositing Minutes of Deed - Nur Maryanto (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
The purpose of this study is to analyze: 1). Law enforcement against a notary who is negligent in keeping the minutes of deed in Pemalang Regency. 2) Obstacles and solutions in enforcing the law against a notary who neglects to keep the minutes of deed in Pemalang Regency. The approach method in this research is empirical juridical with the help of primary data or empirical data as the main data. The data used are primary and secondary data obtained through interviews and literature study, data analysis was carried out by analytical descriptive. The results of the research concluded: 1). Law enforcement against a notary who neglects to keep the minutes of deed in Pemalang Regency, namely starting with the submission of a report, summons and examination by the MPD, as well as the conduct of a trial by the MPW. Sanctions against a Notary who is proven to have violated the provisions of Article 16 paragraph (1) letter b, as regulated in Article 85, the sanctions are in the form of verbal warning, written warning, temporary dismissal, honorable discharge and dishonorable dismissal. The toughest sanctions imposed on notaries who violate the code of ethics and the Law on Notary Positions.